2021
DOI: 10.1371/journal.pone.0251412
|View full text |Cite
|
Sign up to set email alerts
|

C1ql1 is expressed in adult outer hair cells of the cochlea in a tonotopic gradient

Abstract: Hearing depends on the transduction of sounds into neural signals by the inner hair cells of the cochlea. Cochleae also have outer hair cells with unique electromotile properties that increase auditory sensitivity, but they are particularly susceptible to damage by intense noise exposure, ototoxic drugs, and aging. Although the outer hair cells have synapses on afferent neurons that project to the brain, the function of this neuronal circuit is unclear. Here, we created a novel mouse allele that inserts a fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
4
1
Order By: Relevance
“…But it is unlikely due to reduction of afferent and/or efferent innervation as previous studies showed that denervation of efferent innervation did not impact hair cell survival. We note that a recent study showed that OHCspecific deletion of C1ql1 did not reveal a compelling auditory phenotype (Biswas et al, 2021). We would like to point out that this is different from our study where C1ql1 was unquietly deleted in hair cells and neurons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…But it is unlikely due to reduction of afferent and/or efferent innervation as previous studies showed that denervation of efferent innervation did not impact hair cell survival. We note that a recent study showed that OHCspecific deletion of C1ql1 did not reveal a compelling auditory phenotype (Biswas et al, 2021). We would like to point out that this is different from our study where C1ql1 was unquietly deleted in hair cells and neurons.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not label these fibers using specific markers. However, a recent study showed that conditional deletion of C1ql 1 only in OHCs reduced OHC afferent synapse maintenance ( Biswas et al, 2021 ). We evaluated OHC function in C1ql1 KO mice by measuring DPOAE.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found limited cochlear pathological alterations in animal models deficient in the classical complement molecule C1qa ( 86 ). Hair cell specific complement C1q like 1 ( C1ql1 ) deletion leads to no changes in hearing sensitivity ( 15 ), however, a significant hearing loss together with auditory nerve pathology has been reported in the global C1ql1 deficiency model ( 16 ). The alternative complement pathway is responsible for ~80% of complement activity ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the potential role of classical complement signaling in auditory function. For instance, C1ql1 is expressed in the outer hair cells of young adult mice ( 15 ) and global C1ql1- deficient mice show a decline in hearing sensitivity and pathological alterations in the auditory nerve and outer hair cells ( 15 , 16 ). Additionally, levels of complement factor I (CFI, known as C3b/C4b inactivator) were increased in the sensory epithelium following noise trauma in a rodent model ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…C1QL1 has been reported to encode a 258-amino-acid polypeptide with a hydrophobic signal sequence, a collagenous region, and a globular domain at the carboxyl terminus that shares homology with the C1q signature domain [ 6 ]. In a previous study, the expression of C1QL1 was essential for the development of hair cell innervation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%